PTH-126 Azathioprine, steroids and the presence of inflammatory bowel disease before liver transplantation influence transplant free survival in primary sclerosing cholangitis. (22nd June 2015) - Saffioti, F; Manousou, P; Aspite, S; Chatzidis, D; Marshall, A; Pinzani, M; Thorburn, D
Abstract : Introduction: Primary sclerosing cholangitis (PSC) is a chronic, cholestatic liver disease, progressive in the majority of cases. Currently the only therapeutic option is liver transplantation (LT). We assessed potential factors affecting the severity of PSC, comparing patients not needing LT and those who died or were transplanted. Method: Between 1990 and 2013, 370 consecutive patients with PSC have been diagnosed and followed-up. Data was collected retrospectively and Cox-regression analysis was used to evaluate factors known to affect disease severity: demographics (sex and age at diagnosis), inflammatory bowel diseases (IBD) type (ulcerative colitis, Crohn's disease, indeterminate colitis), duration from diagnosis and colonic extent, IBD activity in the last 5 years, IBD treatment during the whole follow-up period (steroids, azathioprine (AZA), anti-TNF, surgery), disease severity at last colonoscopy (before last follow-up or LT), prevalence of colorectal dysplasia/cancer, PSC severity at last follow-up before LT (serum albumin, bilirubin and decompensation), UDCA treatment, cholangiocarcinoma, outcome. Follow-up was censored at time of LT, death or at last follow-up. Results: 333 patients were diagnosed with PSC, 16 with small duct PSC, 21 with autoimmune overlap. 234 (63%) were male, median age at diagnosis 41 years. 138 (41%) were transplanted at a median of 40 months from diagnosis. 62 (17%) died at a median of 94 months from diagnosis. 246 (67%) were diagnosed with IBD: 208 ulcerative colitis, 30 Crohn's disease, 8 indeterminate colitis. 20 had colon cancer, 13 dysplasia. 66 underwent colectomy. Cox regression analysis revealed that factors associated with transplant free survival were: AZA use before transplantation (p = 0.012, OR 2.3, 95% CI 1.2–4.4), treatment with steroids pre-LT (p = 0.001, OR 4.7, 95% CI 2.2–10.1) and concomitant IBD (p = 0.023. OR 2.11, 95% CI 1.11–3.4). A total of 53 patients were on AZA before LT: 7 were transplanted at a median of 62 months and 5 died at a median of 105 months from diagnosis. Of 318 patients not on AZA: 131 underwent LT and 57 died at a median of 44 months and 82 months after the diagnosis. The only factors associated with survival, however, were age at diagnosis <40 years (p = 0.01, OR 1.03, 95% CI 1.01–0.03) and the absence of hepatobiliary malignancy (p = 0.03, OR 0.7, 95% CI 0.5–0.99). Conclusion: In our big cohort of patients affected by primary sclerosing cholangitis, use of AZA and steroids before LT significantly prolonged transplant free survival. Patients with concomitant IBD had an increased transplant free survival compared to those without IBD. Disclosure of interest: F. Saffioti: None Declared, P. Manousou: None Declared, S. Aspite: None Declared, D. Chatzidis: None Declared, A. Marshall: None Declared, M. Pinzani: None Declared, D. Thorburn Grant/ Research Support from: Boston Scientific to fund a clinical research fellow.